The Line of Beijing in Settlement of Problems in the Basin of the South China Sea - V. Y. Vorobyev; A. V. Ivanov (Vestnik MGIMO-Universiteta)
The article is devoted to the politics of China in resolving the problems in the basin of the South China Sea. Not that long ago, the conflict in the region was understood as a clash between China and several countries in South-East Asia, the members of ASEAN (Philippines, Vietnam, Malaysia, Brunei, Indonesia in part), upon the right to own more than one group of uninhabited islands, reefs and shoals scattered throughout the South China Sea, and the limits of their exclusive economic zones and continental shelf. Now, however, opponents of China in the dispute over the islands, who had previously been negotiating with Beijing on a bilateral basis, have taken the first step towards the internationalization of the debate. Meanwhile, China continues to maintain a clear negotiating tactic with its opponents in the dispute over the islands on a strictly bilateral basis, trying to bring its position to all ASEAN members involved in the dispute through each individual partner. Beijing's apparent unwillingness to take real steps to speed up the adoption of the Code of Conduct can probably be explained by the fear that the Code will be used by ASEAN countries to provide collective pressure on China and limit its activities in the region. The policy which was carried out in the South China Sea by China recently has led to strained relations with the countries of the region and prompted some of them, in particular, the Philippines and Vietnam to intensify defense cooperation with the United States. Being connected both to Europe and the Pacific Ocean by its geographical position, Russia would prefer the territorial disputes in the South China Sea not to grow into a confrontation, especially not to be developed into military actions. The fact that in terms of nautical miles Russia is fairly remoted from the South China Sea does not mean it is detached from the situation in the region and its possible outcomes.